Wild animals biobanks: literature review (Research, Society and Development, 2022)
A biological sample bank or biobank is, by definition, a biological collection of any human, animal, plant, microbial sample, associated with sample data, managed according to technical-scientific standards. The aim of this study was to carry out a retrospective study of wild animal biobanks, emphasizing their importance in species conservation, as well as the maintenance procedures for their formation, data management and challenges. Biobanks must be protected as a huge opportunity for wildlife, through the maintenance of biological samples of DNA, somatic cells, tissues, blood, germplasm and embryos, constituting a fundamental scientific database for protection sketches of species under threat. However, there is a need to improve protocols for a range of samples, with the aim of freezing or minimizing injuries caused by cryoprotectants and cooling or freezing temperatures. Biobanks are fundamental tools to protect and manage wild fauna data, creating a conservation network for the development of species conservation strategies, in conjunction with the impasses imposed by extinction processes.